Telaah Eksistensi Hukum Adat pada Hukum Positif Indonesia dalam Perspektif Aliran Sociological Jurisprudence - Nabilah Apriani; Nur Shofa Hanafiah (Jurnal Hukum Lex Generalis, 2022)
Sociological Jurisprudence seeks to produce a synchronization between certainty between positive law and living law. This study aims to examine the perspective of Sociological Jurisprudence on the existence of customary law in Indonesia and the extent to which customary law has contributed and been adopted into positive Indonesian law. This study uses a juridical-normative method, with descriptive-analytical research specifications that are described qualitatively and sourced from primary, secondary, and tertiary legal materials. This study found that customary law in Indonesia is in line with the flow of Sociological Jurisprudence. In addition, the Indonesian Constitution and several laws and regulations have been accommodated in Positive Law.